TRADITIONAL GAMES AND THEIR CONTRIBUTION TO THE RESPECTFUL CHARACTER IN CHILDREN - Chatarina Adinda Febrianty; Gregorius Ari Nugrahanta (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Abstract This research aims to cultivate the respect character of children aged 6-8 years through the development of traditional games manual book. The method used was the ADDIE type of R&D (Research and Development) development method. The manual book was developed through several stages, namely analyze, design, develop, implement, and evaluate stages. The research subjects involved six children (three girls and three boys) between the ages of 6-8. The research also involved seven teachers who have been certified as professional educators to conduct needs analysis and nine validators as expert judgement. The research results are shown that 1) Traditional games manual book were developed with ADDIE stages, 2) Traditional games manual book shows a quality of 3,770 (scales 1-4) included in the "Excellent" category and the suggestion of "No revision needed", 3) The manual book shows the results of the significance test t(5)= 15,947; p = 0.000 (p < 0.05) with large effect of r = 0.980 which equivalent to 98% and included in the "Big effects" category. This means that the traditional games manual book have a great influence on changing the respectful character in children. The effectiveness level score with the N-gain Score of 85.116% is equivalent to the "High" effectiveness level. Keywords: traditional games; respectful character; manual book.